Reproducibility of hepatic fat fraction measurement by magnetic resonance imaging. Issue 6 (21st November 2012) - Mashhood, Arian; Railkar, Radha; Yokoo, Takeshi; Levin, Yakir; Clark, Lisa; Fox‐Bosetti, Sabrina; Middleton, Michael S.; Riek, Jonathan; Kauh, Eunkyung; Dardzinski, Bernard J.; Williams, Donald; Sirlin, Claude; et al.
Abstract Purpose: To evaluate the reproducibility of magnetic resonance imaging (MRI)‐determined hepatic fat fraction (%) across imaging sites with different magnet types and field strength. Reproducibility among MRI platforms is unclear, even though evaluating hepatic fat fractions (FFs) using MRI‐based methods is accurate against MR spectroscopy. Materials and Methods: Overweight subjects were recruited to undergo eight MRI examinations at five imaging centers with a range of magnet manufacturers and field strengths (1.5 and 3 T). FFs were estimated in liver and in fat‐emulsion phantoms using three methods: 1) dual‐echo images without correction (nominally out‐of‐phase [OP] and in‐phase [IP]); 2) dual‐dual‐echo images (two sequences) with T2* correction (nominally OP/IP and IP/IP); and 3) six‐echo images with spectral model and T2* correction, at sequential alternating OP and IP echo times (Methods 1, 2, and 3, respectively). Results: Ten subjects were recruited. For Methods 1, 2, and 3, respectively, hepatic FF ranged from −2.5 to 27.0, 1.9 to 29.6, and 1.3 to 34.4%. Intraclass correlation coefficients were 0.85, 0.89, and 0.91 for each method, and within‐subject coefficients of variation were 18.5, 9.9, and 10.3%, respectively. Mean phantom FFs derived by Methods 2 and 3 were comparable to the known FF for each phantom. Method 1 underestimated phantom FF. Conclusion: Methods 2 and 3 accurately assess FF. Strong reproducibility across magnet type and strength render them suitable for use in multicenter trials and longitudinal assessments. J. Magn. Reson. Imaging 2013;37:1359–1370. © 2012 Wiley Periodicals, Inc.